study of Comparative the performance of search engines and meta engines - فاطمه زندیان; اصغر مسعودی نصر آبادی; masoomeh latifi; لیلا زادولی خواجه (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2016)
aim: this study is Comparative the performance of search engines and meta search engines in retrieval of information. Methodology:. In order to collect the data, five keywords in various fields of information science and universology were selected and five meta-search engines were investigated. Meta-search engines which were investigated in this study include: Meta crawler, web crawler, Info, Info Space and dog pile. Three search engines joint were also covered which are Google, Yahoo and Bing. the first ten retrieved results of each engine were examined. The performance of ranking results in meta search engines from the viewpoint of users were investigated by using technical method. Furthermore, the performance of ranking results in search engines from the viewpoint of users was evaluated. Result:The research results indicate that among the meta search engines, Info has the best performance in ranking results and evaluating with technical method. Also, Google search engines has the best performance in ranking results among the studied search engines, there is a significant difference in search engines and meta search engines in performance of ranking. But from the perspective of users, there is not a significant difference among ranking performance of results in the meta search engines. Moreover, there is not a significant difference among the studied search engines in performance of ranking results. From the viewpoint of users, performance of ranking was conducted better in search engines than in meta search engines, in a way that performance of ranking in meta search engines was at a weak level.